Novels 1926-1929 : Soldier's pay ; Mosquitoes ; Flags in the dust ; The sound and the fury - Faulkner, William, 1897-1962 (The Library of America, 2006)
Svazek obsahuje čtyři romány, které W. Faulkner napsal v letech 1926 až 1929
Chronologický přehled
Keywords: americké romány; výbory; American fiction; selected works